2020
DOI: 10.1002/biof.1633
|View full text |Cite
|
Sign up to set email alerts
|

COVID‐19, pulmonary mast cells, cytokine storms, and beneficial actions of luteolin

Abstract: Dear EditorThe new coronavirus (severe acute pulmonary syndrome [SARS]-CoV-2) originated in China, where it spread rapidly, 1 and has reached pandemic proportions because of its high rate of infectivity as well as high morbidity and mortality, associated with This coronavirus infects by first binding to the ectoenzyme angiotensinconverting enzyme 2 (ACE 2 ), 3,4 a serine protease acting as the receptor, while another serine protease is necessary for priming the viral "S" protein required for entering the cell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
160
0
4

Year Published

2020
2020
2022
2022

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 133 publications
(164 citation statements)
references
References 42 publications
0
160
0
4
Order By: Relevance
“…Mast cells secrete L-6, IL-1, IL-31, IL-33 and TNF, and chemokines CC5, CCL2, MCP-1 and CXCL8 which attract white blood cells to the inflammatory sites. Experiments with coronavirus in mice have shown that this pathogenic RNA microorganism can activate the cells of both innate and adaptive immune systems, including MCs (19,20).…”
Section: Discussionmentioning
confidence: 99%
“…Mast cells secrete L-6, IL-1, IL-31, IL-33 and TNF, and chemokines CC5, CCL2, MCP-1 and CXCL8 which attract white blood cells to the inflammatory sites. Experiments with coronavirus in mice have shown that this pathogenic RNA microorganism can activate the cells of both innate and adaptive immune systems, including MCs (19,20).…”
Section: Discussionmentioning
confidence: 99%
“…The pulmonary pathology associated with COVID-19 appears to result from release of multiple pro-inflammatory cytokines, especially IL-6, that can damage the lungs. 3 A key source of such cytokines and chemokines is the mast cells, which are ubiquitous in the body, especially the lungs, and are critical for allergic and pulmonary diseases. 3 In fact, activated mast cells were recently detected in the lungs of deceased patients with COVID-19 and were linked to pulmonary edema, inflammation and thromboses.…”
mentioning
confidence: 99%
“…Some of these plant foods such as winter squash are also excellent sources of protease inhibitors that are bioavailable and can help prevent blood clotting, a death causing factor in COVID-19 (Otlewski and Krowarsch, 1996). When minimally processed, these foods can serve as good sources of protease inhibitors that can deliver these bioactives daily and may help individuals fight SARS-CoV-2 in-Food science research contribution to SARS CoV-2 and COVID-19 Losso fection (Otlewski and Krowarsch, 1996;Srikanth and Chen, 2016;Theoharides, 2020). The rate of SARS-CoV-2 infectivity and COVID-19-induced mortality appears to be low in countries where minimally processed foods rich in protease inhibitors are consumed regularly and in sizable quantities.…”
mentioning
confidence: 99%